KONTROVERSI PENGGUNAAN KISAH ISRAILIYYAT DALAM MEMAHAMI AYAT-AYAT KISAH AL-QURâAN - Munirah, Munirah (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
How many people like to read a lot of varian of stories in the previous era until now. So, many scholars or teachers and the others use the story telling method to interest the audiens. In religion, it can found many interesting stories in the Holy Book, Taurat and Injil. In the Qurâanic studies, the stories are known as Israliyyat stories. While the Qurâan also told some stories of the prophets, etc in the narrative verses. For understanding the narrative verses, the scholars sometimes use Israiliyyat stories to maintain them. However, some mufassirs have various thoughts about using them. Some interpret the Qurâan with Israiliyyat for detail stories, but some others leave it and just take the lessons. This article analyze the controversy on using Israiliyyat stories to interpret the Qurâan with library research and qualitative method. The conclusion is the scholars base on their thoughts of Israiliyyat can be divided to three category; rejectionees like al-Alusi, Muhammad Abduh, Muhammad Rasyid Ridha, receptionees like Muqatil bin Sulaiman, al-Saâlabi, al-Bagawi, al-Khazin, al-Thabari, and moderatÂ  like Ibnu Taimiyah, Ibnu Kasir. The classification appeared because they actually have various understanding of hadis and different background.